Criteria for a comprehensive assessment of youth's health and behavior according to the results of the questionnaire (Environment & Health, 2025)
The purpose of the study was to develop criteria for a comprehensive assessment of health-forming behavior of young people based on lifestyle analysis and self-assessment of health.Materials and methods. The source of the initial information was the survey data of young people aged 15 to 24 years old. The methods used are: theoretical (analysis and generalization of literary sources; empirical (questionnaire survey) and methods of mathematical statistics (correlation analysis, regression analysis, Student and Pearson test; data rescaling method).Results. An analysis of the received questionnaire data was carried out regarding the state of health of young people and healthy lifestyle habits. The components and factors affecting the health-forming behavior of young people have been determined. The basis of the approach to the calculation of the criteria for comprehensive assessment of the state of health and behavior of young people is proposed. It has been proven that in order to maintain general health, it is necessary to do sports at least 2 times a week. The best effect will be with three times of training. It is recommended to stay in the air for at least two hours a day. Using the phone for more than six hours a day affects well-being, and using it for more than eight hours a day can lead to a noticeable deterioration in health. Working overtime at home for more than four hours is harmful to health. Working at a computer begins to harm at four hours of operation a day, and at six hours - health problems can be quite noticeable. Smoking even one cigarette a day can make you feel worse. Regular consumption of alcoholic beverages stronger than beer and wine on a weekly or daily basis will have negative consequences. The majority of respondents partially adhere to the diet, which is necessary to maintain general health.Conclusions. The expediency of supplementing the assessment of the impact of any factors on health with an indicator characterizing the ratio of «negative» and «positive» components of this impact is shown. It has been proven that the lower threshold of well-being is at least a 10 percent excess of «healthy» habits over «unhealthy» ones, and an excess of almost twice as much contributes to a significant improvement in positive self-assessment of health.
Keywords: questionnaire; self-assessment of health; health-forming behavior; comprehensive assessment criteria